ANALISIS KEBIJAKAN PENDIDIKAN MERDEKA BELAJAR KAMPUS MERDEKA - Andi Nirmayanthi; Yuspiani Yuspiani; Wahyuddin Naro; A., Nurhidayah Br (CV. ADIBA ASIHA AMIRA, 2024)
The Merdeka Belajar Kampus Merdeka (MBKM) policy has become a major focus in improving the quality of higher education in Indonesia. This policy analysis aims to explore the implementation of MBKM, the challenges faced, and its impact on students and higher education institutions. A qualitative approach collected data through a literature review and analysis of related policy documents. The analysis results indicate that MBKM provides significant benefits in expanding students' learning opportunities, enhancing graduates' competencies, and fostering creativity and independence. However, the implementation of MBKM also faces several challenges, such as expanding communication, improving facilities, and adapting policies at the institutional level. Nevertheless, MBKM is expected to bring positive changes to the higher education landscape in Indonesia by empowering students with a more active and autonomous role in their learning. Further research is needed to better understand the effectiveness and efficiency of MBKM implementation in Indonesia's higher education context.